2004
DOI: 10.1593/neo.04262
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pancreatic Cancer Using Serum Proteomic Profiling

Abstract: In the United States, mortality rates from pancreatic cancer (PCa) have not changed significantly over the past 50 years. This is due, in part, to the lack of early detection methods for this particularly aggressive form of cancer. The objective of this study was to use high-throughput protein profiling technology to identify biomarkers in the serum proteome for the early detection of resectable PCa. Using surface-enhanced laser desorption/ionization mass spectrometry, protein profiles were generated from sera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 27 publications
0
57
0
2
Order By: Relevance
“…All solution additions and washes were done using a Biomek 2 robotic liquid handling system (Beckman Coulter, Fullerton, CA). Each chip was analyzed in a Ciphergen SELDI PBSII reader as described (22).…”
Section: )mentioning
confidence: 99%
“…All solution additions and washes were done using a Biomek 2 robotic liquid handling system (Beckman Coulter, Fullerton, CA). Each chip was analyzed in a Ciphergen SELDI PBSII reader as described (22).…”
Section: )mentioning
confidence: 99%
“…Further characterization and sequencing of these key features should provide new insights into disease etiology, and presumably, intervention (33). Surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF MS) has emerged as the primary investigator-based modality for biomarker discovery of early stage cancers (31,34), although the approach does have some limitations that have been identified of late (35,36).…”
Section: Functional Annotation Of Gene Expression Profilingmentioning
confidence: 99%
“…These include reproducibility, contributory effects of nonspecific interference by circulatory molecules unrelated to tumor biology, and the lack of standardization of specimen collection, preparation, and techniques used in detecting differentiating m/z peaks, among others. These valid concerns are continually being addressed (34,41). However, it is critical to note that the pipeline of new biomarkers for cancer diagnosis and/or for tracking cancer progression is drying up (42,43).…”
Section: Functional Annotation Of Gene Expression Profilingmentioning
confidence: 99%
“…15 (25), CA195 (26), TATI (27), POA (28 -30), YKL-40 (31), TUM2-PK (32). Other markers such as peptides identified by surface-enhanced laser desorption and ionization (33,34), and other markers such as MUC4 (35) and synuclein (36) may prove useful but await confirmatory studies and assays optimized for serum analysis. We recently showed that combined serum MIC-1 and CA19-9 measurements had superior diagnostic utility compared with CA19-9 alone for differentiating patients with pancreatic cancer from those without periampullary neoplasia (15).…”
mentioning
confidence: 99%